A research note on the benefit of patient and public involvement in research: The experience of prostate cancer patients regarding information in radiotherapy. Issue 2 (May 2017) - Gordon, L.; Dickinson, A.; Offredy, M.; Smiddy, J.
Abstract: Aim: To explore the inclusion of patient and public involvement (PPI) in a qualitative study on the experiences of men with prostate cancer regarding information in radiotherapy. Method: The application of PPI to one doctoral research study is explored with respect to two perspectives: firstly, involvement of a patient reference group who informed the research design and materials, and secondly, the involvement of a public involvement in research group (PIRg) in advising the researcher during the design process. Discussion: PPI is recognised as an important component of contemporary health research. PPI is becoming a common and essential requirement for high quality research projects and yet literature exploring or reporting the involvement and influence of PPI is sparse. Consideration is given to the national PPI landscape that has shaped public involvement in health research. Conclusion: The contribution of PPI to this study appears to have been beneficial to the development and evaluation of the study design, the self-worth of the reference group participants and demonstrates that the value of PPI in health research should not be underestimated. Highlights: Patient and public involvement (PPI) in research is rare or rarely described. PPI involvement was a positive inclusion and modified the research aims and methods. PPI is of value to both PPI contributors and researchers.